Risk assessment in COVID‐19: Prognostic importance of cardiovascular parameters. Issue 9 (5th July 2022) - Zdanyte, Monika; Martus, Peter; Nestele, Jeremy; Bild, Alexander; Mizera, Lars; Glatthaar, Andreas; Petersen Uribe, Álvaro; Emschermann, Frederic; Henes, Jessica‐Kristin; Geisler, Tobias; Müller, Karin; Gawaz, Meinrad; et al.
Abstract: Background: Cardiovascular risk factors and comorbidities are highly prevalent among COVID‐19 patients and are associated with worse outcomes. Hypothesis: We therefore investigated if established cardiovascular risk assessment models could efficiently predict adverse outcomes in COVID‐19. Furthermore, we aimed to generate novel risk scores including various cardiovascular parameters for prediction of short‐ and midterm outcomes in COVID‐19. Methods: We included 441 consecutive patients diagnosed with SARS‐CoV‐2 infection. Patients were followed‐up for 30 days after the hospital admission for all‐cause mortality (ACM), venous/arterial thromboembolism, and mechanical ventilation. We further followed up the patients for post‐COVID‐19 syndrome for 6 months and occurrence of myocarditis, heart failure, acute coronary syndrome (ACS), and rhythm events in a 12‐month follow‐up. Discrimination performance of DAPT, GRACE 2.0, PARIS‐CTE, PREDICT‐STABLE, CHA2‐DS2‐VASc, HAS‐BLED, PARIS‐MB, PRECISE‐DAPT scores for selected endpoints was evaluated by ROC‐analysis. Results: Out of established risk assessment models, GRACE 2.0 score performed best in predicting combined endpoint and ACM. Risk assessment models including age, cardiovascular risk factors, echocardiographic parameters, and biomarkers, were generated and could successfully predict the combined endpoint, ACM, venous/arterial thromboembolism, need for mechanical ventilation, myocarditis, ACS, heart failure, and rhythm events. Prediction of post‐COVID‐19 syndrome was poor. Conclusion: Risk assessment models including age, laboratory parameters, cardiovascular risk factors, and echocardiographic parameters showed good discrimination performance for adverse short‐ and midterm outcomes in COVID‐19 and outweighed discrimination performance of established cardiovascular risk assessment models.